Geographic routing protocol in mobile ad-hoc networks for reliable FTP traffic communication - Uddin, Jia; Kim, Jongmyon (© 2014 International Information Institute Ltd., 2016)
This article was published in theInternational Information Institute (Tokyo). Information [© 2014 International Information Institute] the Journal's available at :http://search.proquest.com/openview/fe5fe3882d75fd1019431060b33d5da5/1?pq-origsite=gscholar